Whipped Cream Based Mocktail Training for the student of SMA 3 Batam - Natal Olotua Sipayung; Syafruddin Rais; Tito Pratama; Dailami; Siska Amelia Maldin; Rezki Alhamdi; Moh. Thandzir; Wahyudi Ilham; al Ahmed Hatta Wardana Rizqi (JURNAL KEKER WISATA, 2026)
The rapid development of the creative beverage industry has created opportunities for product innovation that emphasize not only taste but also visual appeal and consumer experience. This Community Service Program (PKM) aimed to improve the knowledge, skills, and creativity of students at SMAN 3 Batam through training in the preparation of whipped cream-based mocktails. The implementation methods included lectures, demonstrations, hands-on practice, and product development mentoring. The training materials covered an introduction to mocktails, ingredient mixing techniques, the use of whipped cream, sanitation and hygiene practices, as well as attractive beverage presentation techniques. The results of the program showed that participants were able to understand the basic concepts of mocktail preparation, master beverage preparation and presentation techniques, and produce mocktail products with appealing taste and appearance. Keywords: mocktail, whipped cream, training, high school students, community service.